(3OjhGf GdeJfHjs - (3CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO Hf GdLYaj Gdchaj GdeJfHj, CHh GdWjH, J (B354 (3g` s
(3ChdgG (B:s
(3hdO CHhGdWjH GdeJfHj HGdchaI SfI KdGK hKdGKeGFI hbGd GdTYQ UHjkG aef Chd eG bGdg(B: (3CHcj Gdghi CUaG jhe Gdfhi HOfj haQb GdgLQ Hjf GdLaf hGdhSf s
(3BNQgG (B:s
(3nMji ef Edgj Cf jQGfj hbO aGQbJ OGQc hGUWaGcG bGd GdNGdOj(B: (3gPg GdbUjOI BNQ TYQ bGdg Ke NQL ef TjQGR ojQjO GdYQGb abJd aj GdWQjb s
(3GdfSNI HgG MhGTs
(3fSNI SGOSI eKd GdfSNI GdNGeSIs
(3hQO CjVkG JMJ Qbe (B873(3, (B917(3, (B2191(3, (B2195s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B195 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B809s
Keywords: (3GdCOHs